PERFORMANCE ON THE DROP IMPACT TEST OF THE CONE CAPSULE SHAPED PORTABLE TSUNAMI LIFEBOAT USING PENALTY METHOD CONTACT ANALYSIS - Zakki, Ahmad Fauzan; Suharto, Suharto; Bae, Dong Myung; Windyandari, Aulia (Journal of Applied Engineering Science, 2019)
In 2016, the Laboratory of Ship Structures and Construction Diponegoro University organized a research group to develop an alternative hull form for the tsunami lifeboat. The research group proposed a cone capsule shaped portable tsunami lifeboat to support tsunami evacuation system, especially to give a portable protection facility that easily accessed by disable person, senior citizens and children. In order to fulfill the requirement that the lifeboat structure should be able to withstand the impact load, the aimed of the study is focused on the performance of the drop impact test of the developed portable tsunami lifeboat using numerical simulation. The tsunami lifeboat has to maintain its structural integrity when dropped on 3m free fall height. The orientation configurations are considered for the numerical analysis includes end drop, side drop and reversed drop. The explicit finite element with penalty method contact analysis is used to evaluate the drop test performance. The results show that the maximum effective stress and plastic strain is found in the side drop condition. It is indicated that the side structure is more vulnerable than the top and bottom structure. The maximum absorbed rupture energy is occurred on the frame structure for reversed drop condition, however it is transmitted effectively to all of the connected frames, outer-shell and inner-shell structures. According to the results of simulation analysis, it can be concluded that the structure of the cone capsule tsunami lifeboat is reliable to withstand the severe load during the tsunami disaster.